Applied of BULEYUR technology to empower the economy of communities affected by Covid-19 in Nyatnyono, Semarang - Diana Chilmawati; Ristiawan Agung Nugroho (Universitas Muhammadiyah Magelang, 2024)
Pokdakan Partners Mardi Mulyo and Siwarak Mina Sejahtera in Nyatnyono Village, Semarang Regency, face a number of challenges in cultivating catfish, such as lack of technical knowledge and working capital, low understanding of production processing technology, marketing difficulties during the pandemic, and lack of knowledge about the use of social media and the internet to promote catfish and vegetable cultivation products. The aim of this service activity is to provide knowledge, skills, and business capital through the application of BULEYUR technology (catfish and vegetable cultivation) as an effort to empower partners. The methods applied include dissemination of BULEYUR knowledge and technology, processing of harvests, marketing systems, providing grant assistance for production facilities and infrastructure, as well as intensive partner assistance. The results achieved from the activities show that partners know, understand, and apply BULEYUR technology in increasing business production, processing harvests to increase product selling value, and pioneering online marketing technology applications. The total harvest of 30 BULEYUR buckets was quite good, producing 364 kg of catfish and 360 kg of water spinach; fish survival rate reached 84%; and the absolute growth value reached ±90g/head during 16 weeks of maintenance; and the net profit of the business reached Rp. 3,120,000.00. Other activity achievements include increasing harvest yields through the application of catfish processing technology, as well as pioneering an online-based marketing platform to increase business capacity and income for partners.